2011
DOI: 10.1007/s13193-011-0106-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ultrasonic Shears in Patients with Breast Cancer Undergoing Axillary Dissection—A Pilot Study

Abstract: Patients with breast cancer and positive sentinel node biopsy usually require axillary dissection. Different instruments are used for axillary dissection like regular scalpel,monopolar cautery, bipolar cautery etc. All these instruments are having its advantages and disadvantages. Our dept did a pilot study to know the efficacy of ultrasonic shears over cautery for axillary dissection. Parameters considered were cumulative drain amount, number of days with the drain and number of lymphnodes harvested. Ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Other Authors proposed LS to be the superior device in breast surgery and ALND, but also in these cases, the results are not conclusive. In fact, even if pro studies underlined how the LS utilization led to reduced intraoperative time [59][60][61], reduction of drainage output [60,62], conversely, several Authors showed no substantial difference when compared to EC [63][64][65][66], underlining also a not significant reduction of the cost of hospitalization [67].…”
Section: Discussionmentioning
confidence: 99%
“…Other Authors proposed LS to be the superior device in breast surgery and ALND, but also in these cases, the results are not conclusive. In fact, even if pro studies underlined how the LS utilization led to reduced intraoperative time [59][60][61], reduction of drainage output [60,62], conversely, several Authors showed no substantial difference when compared to EC [63][64][65][66], underlining also a not significant reduction of the cost of hospitalization [67].…”
Section: Discussionmentioning
confidence: 99%